Mesenchymal stem cells alleviate psoriasis-like dermatitis in mice by inhibiting TYK2 phosphorylation - Lina LIANG; Qingyan LUO; Huan WANG; Suyun JI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To investigate the effect of mesenchymal stem cells (MSCs) on TYK2 phosphorylation in psoriasis-like dermatitis induced by imiquimod cream in mice. Methods The mouse model of psoriasis-like dermatitis was induced by imiquimod cream (IMQ). The mice were randomly divided into blank group, IMQ group and IMQ+MSC group. The changes in skin lesion severity, epidermal thickness, inflammatory cell infiltration and TYK2 phosphorylation level were compared among the groups by HE staining, immunofluorescence and Western blotting. Results Compared with the blank group, the mice in IMQ group showed erythema, scales and increased PASI score. HE staining showed parakeratosis, Munro's microabscesses and acanthosis. Immunofluorescence showed infiltration of a large number of CD4+T cells and dendritic cells in the dermis. In comparison to IMQ alone, treatment with MSCs lowered the severities of both erythema and scales, and decreased PASI score and dermal infiltration of CD4+T cells and dendritic cells. In addition, the levels of TYK2 phosphorylation in IMQ group were significantly higher than that in blank group (1.233±0.163 vs 0.634±0.117, P<0.05), while the levels of TYK2 phosphorylation in IMQ+MSC group were lower than that in IMQ group (0.501±0.074 vs 1.233±0.163, P<0.05). Conclusion MSCs can alleviate the severity of psoriasis-like dermatitis in mice by inhibiting TYK2 phosphorylation.